2011
DOI: 10.1111/j.1471-4159.2011.07487.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased cerebral matrix metalloprotease‐9 activity is associated with compromised recovery in the diabetic db/db mouse following a stroke

Abstract: Diabetes is a major risk factor of stroke and is associated with increased frequency of stroke and a poorer prognosis for recovery. In earlier studies we have utilized Type 2 diabetic mouse models of stroke and demonstrated that diabetic db/db and ob/ob mice experience larger infarct volumes and impaired recovery associated with greater infiltration of macrophage following hypoxic-ischemic (H/I) insult than their heterozygous non-diabetic db/+ & ob/+ littermates. To obtain a better understanding of the pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 51 publications
3
57
1
Order By: Relevance
“…Our finding that diabetes was an independent predictor of incomplete recanalization after IVT, suggests that ancillary endovascular therapy in diabetic patients with AIS may be warranted owing to limited thrombolytic activity. Importantly, a previous study reminded us that there was no difference in the rate of recanalization and symptomatic intracranial hemorrhagic after intra-arterial therapy between patients with AIS with and without diabetes 19. Therefore, the optimal reperfusion pattern in diabetic patients with AIS needs to be clarified in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that diabetes was an independent predictor of incomplete recanalization after IVT, suggests that ancillary endovascular therapy in diabetic patients with AIS may be warranted owing to limited thrombolytic activity. Importantly, a previous study reminded us that there was no difference in the rate of recanalization and symptomatic intracranial hemorrhagic after intra-arterial therapy between patients with AIS with and without diabetes 19. Therefore, the optimal reperfusion pattern in diabetic patients with AIS needs to be clarified in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with AIS, diabetes with chronic hyperglycemia might disrupt the blood–brain barrier, and increase hemorrhagic transformation after reperfusion 18. Indeed, animal experiments demonstrated that matrix metalloproteinase 9 was increased in diabetic mice, which could lead to increased blood–brain barrier permeability and greater infiltration of inflammatory cells 19. Meanwhile, the higher matrix metalloproteinase 9 activity in diabetic was an important risk factor for infarct size and severity 17.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to renal ischemic injury, diabetic mice are also more susceptible to cardiac (12,30) and cerebral IRI (23). A role for TLR4 and TNF-␣ in the increased susceptibility to myocardial ischemia has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, claudin-5 is a major cell adhesion molecule of tight junctions in brain endothelial cells (29). The destruction of BBB has been considered to be a key step in the disease process of a number of neurological disorders including cerebral ischemia (30). Ischemic stress is reported to alter the expression of the tight junction-associated proteins described above (26).…”
Section: Interaction Of Ischemic Stroke-induced Bbb Disruption and Glmentioning
confidence: 99%
“…Furthermore, recent evidences show that diabetes and/ or hyperglycemia will provoke molecular changes including imbalance in the MMPs/tissue inhibitors of metalloproteases cascade that alter the function and structure of blood vessels, resulting in a compromised BBB (8,30,33). As we have previously demonstrated, since ischemic stress will activate MMP-2 and MMP-9, and will cause edema, it is possible that post-ischemic glucose intolerance might be involved in disruption of BBB via activation of MMPs and exacerbation of the development of neuronal damage (34).…”
Section: Interaction Of Ischemic Stroke-induced Bbb Disruption and Glmentioning
confidence: 99%